Reproducibility and Agreement Between 2 Spectral Domain Optical Coherence Tomography Devices for Anterior Chamber Angle Measurements. Issue 9 (December 2015) - Marion, Kenneth M.; Maram, Jyotsna; Pan, Xiaojing; Dastiridou, Anna; Zhang, ZhouYuan; Ho, Alex; Francis, Brian A.; Sadda, Srinivas R.; Chopra, Vikas
Abstract : Purpose: To compare anterior chamber angle parameters based on the location of Schwalbe line (SL) from 2 spectral domain optical coherence tomography (SD-OCT) instruments and to measure their reproducibility. Methods: Forty-two eyes from 21 normal, healthy participants underwent imaging of the inferior irido-corneal angle with the Spectralis and Cirrus SD-OCT under tightly controlled low-light conditions. SL-angle opening distance (SL-AOD) and SL-trabecular iris space area (SL-TISA) were measured by masked, certified graders at the Doheny Imaging Reading Center using customized grading software. Interinstrument and intrainstrument, as well as interobserver and intraobserver reproducibility of SL-AOD and SL-TISA measurements were evaluated by intraclass correlation coefficients (ICCs) and Bland-Altman plots with limits of agreement (LoA). Results: The mean SL-AOD was 0.662±0.191 mm in Spectralis and 0.677±0.213 mm in Cirrus. The mean SL-TISA was 0.250±0.073 mm 2 in Spectralis and 0.256±0.082 mm 2 in Cirrus. The agreement for intrainstrument (ICCs>0.979), intragrader (ICCs>0.992), and intergrader (ICCs>0.929) was excellent. Excellent agreement between the 2 devices was also documented with a mean difference of −0.016 (LoA −0.125 to 0.092) mm for SL-AOD and −0.007 (LoA −0.056 to 0.043) mm 2 in SL-TISA. Conclusions: Both SD-OCTs provided comparable measurements and permitted calculation of SL-based angle metrics. There was excellent interinstrument and intrainstrument and intraobserver and interobserver reproducibility for Spectralis and Cirrus SD-OCTs, suggesting true interchangeability between SD-OCT devices. This has the potential to lead to development of standardized grading assessments and quantification of angle parameters that would be valid across various SD-OCT devices.